Ligand-mediated reversal of the oxidation state dependent ROS scavenging and enzyme mimicking activity of ceria nanoparticles. Issue 99 (27th November 2018) - Patel, Vaishwik; Singh, Mandeep; Mayes, Edwin L. H.; Martinez, Abraham; Shutthanandan, Vaithiyalingam; Bansal, Vipul; Singh, Sanjay; Karakoti, Ajay S.
Abstract : Enzymatic activity of cerium oxide nanoparticles modified by phosphine ligands. Abstract : Nanoceria is considered as a potent antioxidant (free radical scavenger) and its enzymatic activity is reported to be a function of the oxidation state of surface cerium ions. Here we demonstrate phosphine ligand-dependent enzymatic activity of nanoceria irrespective of its as-synthesized oxidation state.